Driver’s Attitudes about the Impact of Caffeine and Energy Drinks on Road Traffic Safety - Dalibor Pešić; Boris Antić; Davor Brčić; Jelica Davidović (Promet (Zagreb), 2015)
Large amounts of energy drinks and caffeine, which is the main ingredient of energy drinks, produce a negative effect on the drivers, and therefore affect traffic safety. In order to determine the attitudes of drivers toward the impact of energy drinks and caffeine, a research was conducted using a questionnaire form and the targeted group of the survey were drivers. The research was conducted in the City of Belgrade in December 2012. There were 420 survey papers distributed to drivers of different age groups of which 412 were returned. The survey was completely anonymous and consisted of two parts. The first part was related to basic demographic information about the respondents and it had 8 closed type questions. These questions were responded by circling one of the offered answers. The second part of the survey referred to determining the driver’s attitudes about energy drinks and caffeine. The second part consisted of 26 questions and respondents were to use a five-level scale in order to show to what extent they agree or disagree with any of the listed statements. The results show that energy drinks are consumed mostly by young people, less than 25 years old. The effect of caffeine on gender is statistically significant. Headache is the reason why caffeine (25%) is consumed more than energy drinks (8%). Major impact of energy drinks and caffeine on road safety indicates a required activity in this area such as education.